MINI BOOK SEBAGAI MEDIA PENGEMBANGAN KETERAMPILAN MEMBACA SISWA SEKOLAH DASAR - Nur_Kholickun; Atikah Mumpuni; Didik Tri Setiyoko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Reading skills are a fundamental aspect of elementary school education and play an important role in students' literacy development. However, several third-grade students at SD Negeri Klampok 05 still experience delays in reading and have low reading interest. The main factors contributing to this issue are the limited availability of engaging reading materials and the lack of environmental involvement in literacy culture. This study aims to analyze the use of Mini Books in developing students' reading skills. The research method used is descriptive qualitative with a case study approach. Data collection techniques include observation, interviews, and documentation. Data were analyzed using the Miles and Huberman model, which consists of data reduction, data presentation, and conclusion drawing. The results indicate that Mini Books are effective in enhancing reading skills through strategies such as shared reading, interactive reading, read-aloud techniques, and vocabulary reinforcement. Additionally, the implementation of Mini Books involves preparation, execution, reinforcement, and evaluation. A supportive environment, both at school and at home, plays a crucial role in shaping students' reading habits. In conclusion, Mini Books are an effective learning medium for improving students' reading skills, provided they are supported by a conducive learning environment.